Assessing nursing staff's competences in mobility support in nursing-home care: development and psychometric testing of the Kinaesthetics Competence (KC) observation instrument - Gattinger H; Leino-Kilpi H; Hantikainen V; Kopke S; Ott S; Senn B (BIOMED CENTRAL LTD, 2025)
Background: Between 75 and 89% of residents living in long-term care facilities have limited mobility. Nurses as well as other licensed and unlicensed personnel directly involved in resident care are in a key position to promote and maintain the mobility of care-dependent persons. This requires a certain level of competence. Kinaesthetics is a training concept used to increase nursing staff's interaction and movement support skills for assisting care-dependent persons in their daily activities. This study aims to develop and test an observation instrument for assessing nursing staff's competences in kinaesthetics.
Methods: The Kinaesthetics Competence (KC) observation instrument was developed between January and June 2015 based on a literature review, a concept analysis and expert meetings (18). The pilot instrument was evaluated with two expert panels (n = 5, n = 4) regarding content validity, usability and inter-rater agreement. Content validity was assessed by determining the content validity index (CVI). The final instrument was tested in a cross-sectional study in three nursing homes in the German-speaking part of Switzerland between July 2015 and February 2016. In this study nursing staff (n = 48) was filmed during mobilization situations. Based on this video data two observers independently assessed nursing staff's competences in kinaesthetics with the KC observation instrument. Inter-rater reliability and inter-rater agreement was evaluated using the intra-class correlation coefficient (ICC) and percentage of agreement. Construct validity was assessed by a discriminating power analysis. Internal consistency was evaluated using Cronbach's alpha coefficient and item analysis.
Results: The final version of the KC observation instrument comprised of four domains (interaction, movement support of the person, nurses' movement, environment) and 12 items. The final instrument showed an excellent content validity index of 1.0. Video sequences from 40 persons were analysed. Inter-rater reliability for the whole scale was good (ICC 0.73) and the percentage of inter-rater agreement was 53.6% on average. Cronbach's alpha coefficient for the whole instrument was 0.97 and item-total correlations ranged from 0.76 to 0.90. The construct validity of the instrument was supported by a significant discrimination of the instrument between nursing staff with no or basic and with advanced kinaesthetics training for the total score and 3 of 4 subscales.
Conclusions: The KC observation instrument showed good preliminary psychometric properties and can be used to assess nursing staff's competences in mobility care based on the principles of kinaesthetics.